2015
DOI: 10.1007/s12262-015-1380-y
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of Conflict Zone-Related Ballistic Renal Injury

Abstract: To analyze our approaches and experiences in patients with renal injuries accompanying penetrating abdominal injuries admitted to the hospital due to high kinetic energy weapons. Patients including renal injuries associated with penetrating abdominal injuries due to gunshot wounds and fragments of shell treated at our institution between February 2002 and May 2013 were retrospectively analyzed. Total 21 patients were included in this study, 20 of whom (86.2 %) were male and 1 (13.8 %) female. Renal injury was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…No data exist regarding the best management strategy in low resource settings, although it seems rational to use OM in those circumstances. Low resource settings, in a limited sense, could be considered similar to military settings where lack of well-equipped hospital facilities, increased distance from trauma centers, and long transport time to definitive care facilities are the norm [167].…”
Section: Methodsmentioning
confidence: 99%
“…No data exist regarding the best management strategy in low resource settings, although it seems rational to use OM in those circumstances. Low resource settings, in a limited sense, could be considered similar to military settings where lack of well-equipped hospital facilities, increased distance from trauma centers, and long transport time to definitive care facilities are the norm [167].…”
Section: Methodsmentioning
confidence: 99%
“…In the case of blast effects, the authors observed intraoperatively that the liver has a protective effect on the right kidney such that it may sustain the impact of the blast injury. In renal and liver injuries not directly attributable to projectile, although the blast effect caused higher-grade liver injuries, it was observed that a lower-grade right kidney injury occurred at the same time [11] Paquette presented results of a research in which, out of the 2712 trauma cases, 76 (2.8%) out of 98 cases had one or more genitourinary injuries. Out of the 29 kidney injuries, 2 were explored without any treatment, 7 were observed, 1was repaired and 19 casualties required nephrectomy [14].…”
Section: Discussionmentioning
confidence: 99%